The Ethical Implications of Political Deepfakes: A Deontological Perspective on Democratic Communication - Nadia Angelina; Mohd Haizra Hashim (Jurnal Multidisiplin Indonesia, 2026)
The rapid advancement of artificial intelligence has enabled the creation of political deepfakes, raising significant concerns about the integrity of democratic communication. While existing scholarship has primarily focused on technological detection, misinformation, and regulatory responses, limited attention has been given to the ethical implications of political deepfakes from a deontological perspective. This study examined how political deepfakes challenge the principles of truthfulness, honesty, and moral responsibility that underpin democratic communication. Employing a qualitative conceptual approach, the study drew upon media ethics literature, deontological ethical theory, and contemporary research on political deepfakes to analyze the ethical consequences of AI-generated synthetic media in political contexts. The findings indicated that political deepfakes constitute deliberate forms of deception that violate the deontological duty of truthfulness and contribute to the erosion of public trust by generating uncertainty regarding the authenticity of political communication. The analysis further demonstrated that ethical responsibility extends beyond content creators to include political actors, digital platforms, and other stakeholders involved in dissemination. Moreover, the study argued that the broader ethical risk of political deepfakes lies in their capacity to generate an epistemic crisis in which citizens become increasingly uncertain about the reliability of public information. This study contributes to the growing body of literature by extending existing discussions beyond technological and regulatory concerns toward a normative ethical analysis grounded in deontological principles, highlighting the importance of truthfulness, accountability, and moral responsibility in preserving democratic communication in the age of artificial intelligence.